(untitled) (Journal of Fiber Bioengineering and Informatics, 2015)
The main content dealt with in the paper is to analyze effects of structural parameters on compression property of spacer fabrics. Based on compression stress and strain curves, four characteristic indices are featured, which include compression work, recovery ratio of compression work, maximum compression force when compression strain is 0.7 and secant modulus by fitting compression stress - strain curve from strain 0 to 0.25. Experimental results show that structural parameters of spacer fabric, including thickness of spacer fabric and diameter, angle, arrangement shape and density of spacer filament, significantly influence compression behaviour. With the thickness of specimen increasing, compression work increased, while the compression secant modulus and maximum force decreased, and the recovery existed nonlinear relationship and showed a relatively optimal thickness. Compression work, recovery ratio, maximum force and secant modulus existed the same ascending trend when the diameter of spacer filament increased from, while they showed descending trend when spacer angles decreased. The whole structure of spacer fabric was more stable when the arrangement of spacer filament is X-shaped than Vshaped, and the compression work, recovery ratio, maximum force and secant modulus of sample X shape were all larger than those of sample V shape. As for the density of spacer filaments, the compression work, maximum force and secant modulus increased with density decreased, while the recovery ratio of spacer fabric with higher density was smaller than that of smaller density.